WHEN HEALTHCARE BECOMES CRIMINAL POLICY: VACCINATION BEFORE THE CONSTITUTIONAL COURT OF SERBIA (II PART) - Ristivojević, Branislav; Samardžić, Stefan S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
This article is a continuation of the analysis and critique of arguments used by the first Grand Chamber of the Constitutional Court in order to dismiss the 2016 initiative for a constitutional review of provisions of the Law on the Protection of the Population from Infectious Diseases. An analysis of the Court’s circumstantial arguments, such as the case-law of the European Commission of Human Rights and the European Court of Human Rights is provided. Among the circumstantial arguments, as they are referred to in this article, used by the First Grand Chamber of the Constitutional Court to dismiss the initiative for the constitutional review of provisions of the Law on Mandatory Vaccination, we cannot find a single argument that justifies the Court’s decision on dismissal of the initiative. Conflicting and mutually opposing positions with references to outdated and obsolete case-law of the European judicial institutions compiled on the basis of superficial and arbitrary research, the drawing of speculative conclusions, self-censorship and cowardly secretive procedure of enacting the decision on dismissal of the initiative, offer nothing new that would change the conclusions the author arrived at in the first part of this article. The First Grand Chamber of the Constitutional Court joined the legislative branch in strengthening a hybrid legislative policy. This policy is the result of an unnatural mixing between classical health care policy measures and classical measure of penal policy, such is the penalty. This unnatural mix is assessed in the article as “genetically modified legislative policy” that will not fulfill the aims of either policy from which it has borrowed its DNA. Moreover, the conclusion of the second part of the article only strengthened the conclusion reached in the first part of the article that this legislative bastard will wreak havoc on the public health and the criminal justice systems alike.